Odpowiedzi

2010-02-18T18:44:47+01:00
A)x(4x-20)
b)4(x kwadrat - 5x)
c)4x(x-20)
d)20(4/20 x kwadrat - x)
e) 20x(4/20x-x)
f)-x(-4+20)
g)-4(-x kwadrat +5x)
h)-4x(-x+5)
i)-20(-4/20 x kwadrat +x)
j) - 20x(-4/20x+1)
1 1 1
Najlepsza Odpowiedź!
2010-02-18T18:46:44+01:00
4x² - 20x

a) x 4x² - 20x =x(4x-20)
b)4 4x² - 20x =4(x²-5x)
c)4x 4x² - 20x =4x(x-5)
d)20 4x² - 20x =20(1/5x²-x)
e)20x 4x² - 20x =20x(1/5x-1)
f) -x 4x² - 20x = -x(-4x+20)
g)-4 4x² - 20x = -4(-x²+5x)
h)-4x 4x² - 20x = -4x(-x+5)
i)-20 4x² - 20x = -20(-1/5x²+x)
j)-20x 4x² - 20x =-20x(-1/5x+1)
2 5 2
2010-02-18T18:48:08+01:00
A) x
4x²-20x= x(4x-20)
b) 4
4x²-20x= 4(x²-5x)
c)4x
4x²-20x= 4x(x-5)
d)20
4x²-20x= 20(⅕x²-x)
e)20x
4x²-20x= 20x(⅕x-1)
f) -x
4x²-20x= -x(-4x+20)
g)-4
4x²-20x= -4(-x²+5x)
h)-4x
4x²-20x= -4x(-x+5)
i)-20
4x²-20x= -20(-⅕x²+x)
j)-20x
4x²-20x= -20x(-⅕x+1)
1 1 1